The Role of Anatomy in Medical Education - Hossein Bahadoran; Reza Dadfar; Mohammad Hosein Asadi; Sajad Moghadami (Negah Institute for Scientific Communication, 2022)
Anatomical sciences are considered as the foundation of the medical education. Previously, the anatomy in medical educational environments was based on the lecture presentation and corpus dissection. Then, the newer protocols, such as teaching methods using human models, imaging, simulation, and internet-based webinars, were widely used in academic schools. In this era, the medical curriculums focused less on corpse dissection. Medical learning in the field of anatomy was basically based on the traditional approaches and presentation-based learning using the students under the teacher's supervision. The teacher, as the class manager, can design the curriculum contents using clinical applications along with knowledge assessment. This procedure can be achieved through planning for the future and the plans ensuring the persistent development of anatomy as a relevant clinical subject in any medical curriculum.